Effectiveness of different measures to control red bloom in carp ponds - Mandal, R. B.; Rai, S.; Shrestha, M. K.; Jha, D. K.; Pandit, N. P. (Journal of Agriculture and Forestry University, 2022)
Red blooms caused by Euglena sanguinea (Ehrenberg, 1832) might cause severe depletion of dissolved oxygen significantly in the pond. An experiment was conducted to assess the effects of measures for controlling E. sanguinea on water quality, growth and yield of carp polyculture. The experiment included four treatments: without mitigation measure (T1), skimming using net skimmer (T2), fertilization with urea and diammonium phosphate (T3) and liming using agriculture lime (T4) with three replications. The experiment was carried out for 120 days. The results showed that abundance of E. sanguinea was significantly lower (p < 0.05) in urea and diammonium phosphate treated ponds (270 ± 10 cells L-1) than control ponds (1650 ± 90 cells L-1). Water quality parameter such as nitrite, total nitrogen and total phosphorus were significantly (p < 0.05) higher in control ponds (T1) than in treatment ponds. The net fish yield of rohu was significantly higher (0.19 ± 0.0 t ha-1) in T3 ponds than T2 ponds (0.07 ± 0.0 t ha-1). The present experiment effectively controlled abundance of E. sanguinea but admixture of urea and diammonium phosphate application appeared to be better control measures because dissolved oxygen content was at acceptable level in the ponds.